2005
DOI: 10.1525/eth.2005.33.3.367
|View full text |Cite
|
Sign up to set email alerts
|

Agreement between Children's and Mothers' Perceptions of Maternal Acceptance and Rejection: A Comparative Study in Finland and Pakistan

Abstract: The primary purpose of this study was to explore the relative level of agreement or disagreement between mothers' reports versus children's reports of maternal acceptance‐rejection in Finland and Pakistan. Of special interest was the question whether the level of agreement varied significantly in loving families (as defined by children) versus less than loving families (as defined by children). Data were collected from 144 mother/child dyads. The Child version of the Parental Acceptance‐Rejection Questionnaire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
23
0
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 45 publications
0
23
0
3
Order By: Relevance
“…We were unable to examine paternal influence as only a small proportion of informants were fathers (1.8%). Future studies should include a higher number of fathers as their parenting behaviors may be at least as influential as mothers’ (Rohner et al, 2005). Reliability of some parenting practices, which were not PW, was not optimal.…”
Section: Discussionmentioning
confidence: 99%
“…We were unable to examine paternal influence as only a small proportion of informants were fathers (1.8%). Future studies should include a higher number of fathers as their parenting behaviors may be at least as influential as mothers’ (Rohner et al, 2005). Reliability of some parenting practices, which were not PW, was not optimal.…”
Section: Discussionmentioning
confidence: 99%
“…The shortcomings of single report is especially crucial in the case of parental warmth as previous studies have shown that parents, especially mothers, have difficulty reporting reliably on various familial areas, particularly their own loving and controlling behaviors or familial conflict (Gonzales, Cauce, & Mason, 1996). Additionally, child report and parents’ self‐report often do not concur, especially in the case of mothers on warmth (Rohner, Khaleque, Riaz, et al., 2005).…”
Section: Political Violence In Israelmentioning
confidence: 99%
“…This warmth and affection is a range from a great deal to none, where one end is named parental acceptance while the other one is termed rejection (Rohner [12]. The term parent is defined in PARTheory (Rohner., Khaleque., Riaz., Khan., Sadeque., & Laukkala [15] as any person who has a more or less long term care giving responsibility for a child. Such person may be biological or adoptive parents, older sibilngs, grandparents, other relatives or even non-kinspersons.…”
Section: Introductionmentioning
confidence: 99%